PENGARUH MODEL EXPERIENTIAL LEARNING BERBANTUAN ETNOMATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Aulia Tu Zahra; Ihsanudin; Indiana Marethi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the fact that students’ mathematical problem-solving skills remain low. Therefore, appropriate alternative teaching methods are needed to improve these skills. One such method is the application of an experiential learning model supported by ethnomathematics. The purpose of this study is to determine the effect of an experiential learning model supported by ethnomathematics on students’ mathematical problem-solving skills. This study employed a quantitative, quasi-experimental design. The study population consisted of all eighth-grade students at SMP Negeri 1 Kibin, with the sample comprising Class VIII D (the experimental class) with 32 students and Class VIII E (the control class) with 31 students. Instruction in the experimental class utilized the experiential learning model supported by ethnomathematics, while the control class used the expository model. Research data were collected using a mathematical problem-solving ability test. The results of the independent samples t-test showed a Sig. value of 0.004 < 0.05, indicating a significant difference in final mathematical problem-solving ability between the two classes. Further evidence was obtained from the results of the Mann-Whitney test on the N-gain data, which showed a Sig. value of 0.045 < 0.05. This indicates that the improvement in mathematical problem-solving skills among students using the experiential learning model supported by ethnomathematics was greater than that of students using the expository model. Thus, the experiential learning model supported by ethnomathematics has a significant effect on students’ mathematical problem-solving skills.